Transmission Of The Values Of Monotheism Through Digital-Based Educational Games: Innovation In Islamic Religious Education In The Gen Z Era - Idhan, Mohamad (PT. Anagata Sembagi Education, 2025)
The development of digital technology has given birth to a new generation characterized by visual, interactive learning, and integration with digital media. Generation Z requires a religious education approach that is adaptive to their learning style, especially in transmitting the value of monotheism as the core of Islamic teachings. This study aims to explore the effectiveness of digital educational games in transmitting the value of monotheism to elementary school students. The approach used was a qualitative case study method at one of the Islamic Elementary Schools in South Jakarta that applies digital media in Islamic Religious Education learning. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation studies. The results of the study indicate that educational games based on the value of monotheism are able to create an immersive and reflective learning experience, as well as improve students' spiritual understanding cognitively and affectively. Visual narratives, moral challenges, and interactivity in the game become effective means of internalizing values that are relevant to the characteristics of Generation Z. The conclusion of this study emphasizes the importance of integrating religious content and technology in transformative learning design. The transmission of the value of monotheism through digital educational games has proven to be an innovative strategy in grounding spiritual values in the digital era full of ideological and cultural challenges.